La fréquence d’utilisation de la tablette numérique à des fins pédagogiques et le rendement scolaire des élèves : le rôle médiateur de la motivation autodéterminée - Supper, Wilfried; Guay, Frédéric; Falardeau, Érick; Karsenti, Thierry; Pelletier, Guillaume (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
The objectives of this research are to test whether the frequency of use of the digital tablet (DT) as a teaching tool in the classroom is associated with the students' academic performance in mathematics, in French and in English, and if this relation is explained by greater students’ autonomous motivation. Our results, obtained from structural equation modeling, indicate that a more frequent use of the DT positively predicts autonomous motivation in mathematics and French school subjects. We discuss the meaning of these findings for the scientific literature on DT and for self-determination theory.